The supervised internship and extension as a space for dialogue between university and school - de Menezes, Priscylla Karoline (Revista Ensino de Geografia (Recife), 2022)
Resulteof reflections generated from an extension action, carried out with students of the Degree in Geography at the Federal University of Pernambuco, this study sought to understand the role of the curriculum in the Teaching of Geography and the changes that occurred in the initial formation according to the changes caused by emergency remote teaching -implemented due to the need for social isolation. In this sense, we resume some readings and fragments of the part that deals with training and teaching work and we seek to reflect on the experience of the discussions and the realization of the event entitled I Seminar of Internship of Degree in Geography at UFPE; which allowed us to visualize the importance of building spaces for dialogue within Teaching Institutions, involving University and Basic Education, for a true social intervention and in the process of teacher training.